2011
DOI: 10.5120/2904-3813
|View full text |Cite
|
Sign up to set email alerts
|

Unified System Level Fault Modeling and Fault Propagation

Abstract: Fault modeling is an important step towards both understanding and validating the implemented system. The focus of the paper is to present a unified system fault modelling framework, including input related faults model based on system theory. The complex embedded system (CES) is modelled using sequence of communicating FSM (SCFSM) and the system faults are represented by two components of system fault vector -system behaviour fault vector and system communication fault vector. These two system fault vector co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The integration testing of MDS can be viewed as identification of faulty communication channel [30,43] or faulty machine [30,44] problem. It is shown that mathematical functions and logical expressions can be used as, partial specifications and test data can be automatically generated [41].For the integration testing the idea of faulty communication channel is very logical, as the objective of integration testing is to uncover errors in the interaction between the components and their environment.…”
Section: Step4-verificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The integration testing of MDS can be viewed as identification of faulty communication channel [30,43] or faulty machine [30,44] problem. It is shown that mathematical functions and logical expressions can be used as, partial specifications and test data can be automatically generated [41].For the integration testing the idea of faulty communication channel is very logical, as the objective of integration testing is to uncover errors in the interaction between the components and their environment.…”
Section: Step4-verificationmentioning
confidence: 99%
“…The DOP model specifies necessary information for development and also test generation. To efficiently test any system, it is important to know the possible failures, causes and the way they propagate [30]. The first step is the identification and classification of design faults that occur during the early developmental stages.…”
Section: Evaluation Of Prototypementioning
confidence: 99%
See 1 more Smart Citation